An Adapted Firefly Algorithm for Product Development Project Scheduling with Fuzzy Activity Duration. (17th March 2015) - Huang, Minmei; Yuan, Jijun; Xiao, Jing
Abstract : Efficient scheduling plays an important role in product development project management, especially for the product development project with fuzzy activity times. In this research a trapezoidal fuzzy number is used to represent fuzzy activity duration, and an improved magnitude of the trapezoidal fuzzy number is adopted for fuzzy time comparison. Firstly, a mathematical model for the scheduling problem with minimizing the project completion time for the product development project is established. Then, an adapted fuzzy firefly algorithm is developed to solve the model. The priority value based coding method is used; the fuzzy parallel schedule generation scheme is adopted to generate feasible solutions, and the brightness comparisons are made before updating fireflies' locations in the proposed algorithm. Finally, the performance of the proposed algorithm is presented by computational experiments based on PSPLIB benchmarks. An example of resource allocation of an electronic product development project is also used to illustrate the effectiveness and efficiency of the proposed algorithm.